The Implementation of WhatsApp Group in An EFL Classroom - Selvianah Selvianah; Achmad Taqlidul Chair Fachruddin; Nihla Afdaliah (LETS: Journal of Linguistics and English Teaching Studies, 2021)
This research aims to see the implementation of WhatsApp media in EFL Classroom. Researcher used qualitative descriptive data collection through observation to see the learning process that took place in WhatsApp group, then interviewed students and teacher, and finally documentation. Data analysis techniques in this research are data reduction, data presentation and conclusion drawing. From the research results, it can be seen that the learning process is divided into three stages, namely: 1) Planning, 2) Implementation which is divided into three stages, namely: opening, core and closing activities and 3) evaluation. In this case, students can still participate in the learning process using WhatsApp group and easily accessible, save quota and also have various features that teacher can choose to use in the learning process such as WhatsApp groups, chat messages, document files, videos or photos. In addition, there are still obstacles that faced by teacher and students such as teacher cannot observe directly, learning is not optimal, poor internet network, full cellphone memory or lack of understanding of the material.